2007
DOI: 10.1038/sj.mp.4002101
|View full text |Cite
|
Sign up to set email alerts
|

The amyloidogenic potential and behavioral correlates of stress

Abstract: Observations of elevated basal cortisol levels in Alzheimer's disease (AD) patients prompted the hypothesis that stress and glucocorticoids (GC) may contribute to the development and/or maintenance of AD. Consistent with that hypothesis, we show that stress and GC provoke misprocessing of amyloid precursor peptide in the rat hippocampus and prefrontal cortex, resulting in increased levels of the peptide C-terminal fragment 99 (C99), whose further proteolytic cleavage results in the generation of amyloid-b (Ab)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
117
1
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(139 citation statements)
references
References 68 publications
18
117
1
3
Order By: Relevance
“…It is likely that social isolation led to oxidative stress (Schiavone et al, 2009), which in turn stimulated b-and g-secretase activity (Chan et al, 2009) resulting in increased Ab, which then triggered onset of cognition decline in the APP/PS1 mice. These results are consistent with previous reports showing that stress and glucocorticoids similarly promote APP processing along the amyloidogenic pathway (Catania et al, 2009) resulting in the exacerbation of AD-like neuropathology (Billings et al, 2005;Green et al, 2006;Jeong et al, 2006;Srivareerat et al, 2009).…”
Section: Acceleration Of Memory Impairment By Social Isolationsupporting
confidence: 83%
“…It is likely that social isolation led to oxidative stress (Schiavone et al, 2009), which in turn stimulated b-and g-secretase activity (Chan et al, 2009) resulting in increased Ab, which then triggered onset of cognition decline in the APP/PS1 mice. These results are consistent with previous reports showing that stress and glucocorticoids similarly promote APP processing along the amyloidogenic pathway (Catania et al, 2009) resulting in the exacerbation of AD-like neuropathology (Billings et al, 2005;Green et al, 2006;Jeong et al, 2006;Srivareerat et al, 2009).…”
Section: Acceleration Of Memory Impairment By Social Isolationsupporting
confidence: 83%
“…This is in line with the observations that major stressful events lower the age of onset of familial AD (Mejia et al, 2003). In various preclinical AD models, stress worsens deficits in hippocampus-dependent spatial learning (Catania et al, 2009;Cuadrado-Tejedor et al, 2012;Dong et al, 2004;Jeong et al, 2006;Srivareerat et al, 2009;Tran et al, 2010). These deleterious effects are in part caused by an accelerated accumulation of Ab under stressing conditions (Catania et al, 2009;Cuadrado-Tejedor et al, 2012;Dong et al, 2004;Green et al, 2006;Jeong et al, 2006;Srivareerat et al, 2009).…”
Section: Introductionsupporting
confidence: 73%
“…In various preclinical AD models, stress worsens deficits in hippocampus-dependent spatial learning (Catania et al, 2009;Cuadrado-Tejedor et al, 2012;Dong et al, 2004;Jeong et al, 2006;Srivareerat et al, 2009;Tran et al, 2010). These deleterious effects are in part caused by an accelerated accumulation of Ab under stressing conditions (Catania et al, 2009;Cuadrado-Tejedor et al, 2012;Dong et al, 2004;Green et al, 2006;Jeong et al, 2006;Srivareerat et al, 2009). Stress triggers the release of glucocorticoid hormones (CORT), the major output of the hypothalamopituitary-adrenal axis (HPA).…”
Section: Introductionmentioning
confidence: 99%
“…Although no data are available on the effects of A␤ peptide injection on hypothalamic-pituitary-adrenal axis activity, several studies have demonstrated that glucocorticoids modulate APP processing, 55 increase A␤ 1-42 -induced neurodegeneration in basal nuclei of Meynert, 56 and increase A␤ [25][26][27][28][29][30][31][32][33][34][35] toxicity in hippocampus neurons. 57 Moreover, in vivo chronic corticosterone administration was shown to increase A␤ and N-methyl-D-aspartate-induced neurodegeneration in cholinergic neurons from the nucleus basalis in the rat.…”
Section: Discussionmentioning
confidence: 99%